Expression of gene region encoding pre-membrane and envelope antigen of dengu virus type 4 in Pichia pastoris - Hồng Lê Thị Thu; Nguyệt Phùng Thu; Hường Trần Thị; Thanh Nguyễn Hồng; Hồng Phạm Thúy; Kháng Đinh Duy; Hải Trương Nam (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 39-44, 2005